Analisis Kebutuhan Pengembangan Kurikulum dalam Implementasi Meningkatkan Kemampuan Berpikir Kritis Siswa Sekolah Dasar - Susanti, Ari; Sumarno, Sumarno; Dwijayanti, Ida (Medan Resource Center, 2024)
The independent curriculum represents a new educational paradigm aimed at addressing the challenges of the 21st century, focusing on the development of skills such as critical thinking, creativity, collaboration, communication, problem-solving, and digital literacy. Despite these goals, the practical implementation in elementary schools has proven challenging, with student engagement in lessons remaining low. This study seeks to analyze students' critical thinking abilities and teachers' expectations regarding these skills. Using a descriptive qualitative method, data were collected through interviews and observations at SD Negeri Karakan 01, Weru District, Sukoharjo Regency. The findings indicate several obstacles in implementing the Independent and K13 curricula, including inadequate development of ATP and lesson plans tailored to student needs, monotonous teaching models, and difficulties in time allocation for project-based learning. Although evaluation activities are conditionally conducted at the end of each lesson, the overall implementation of both curricula has not effectively enhanced students' critical thinking skills. This study highlights the need for more dynamic teaching approaches and better curriculum development to meet the educational demands of the 21st century.